Kekerasan Simbolik terhadap Orang yang Memiliki Riwayat Penyakit Kusta (Studi pada Warga di Lingkungan Pondok Sosial Para Cacat Eks Kusta di Desa X) - Iga Styowati (Jurnal Kriminologi Indonesia, 2013)
Social problem is one of the biggest problems faced by people affected by leprosy, especiallyin a place called Lingkungan Pondok Sosial Para Cacat Eks Kusta in X village (and thenit will be called as Liposos Paca). Social problem comes from stigma as a result of negativesocial construction. Stigma creates social exclusion and other discrimination actions thatare occurred since they are affected by leprosy until they have cured from leprosy. Analysisabout stigma and social exclusion in this research will be associated with symbolic violencefrom Bourdieu. This research uses qualitative research method especially ethnographyemphasizing on participation observation, depth interview, and literature study. This researchresults that symbolic violence on people affected by leprosy tend to be lasting because of therecognition of the domination of relationship happen.